Subcontracting Microwork - Morris, Meredith Ringel; Bigham, Jeffrey P.; Brewer, Robin; Bragg, Jonathan; Kulkarni, Anand; Li, Jessie; Savage, Saiph (Proceedings of CHI 2017, 2017)
Mainstream crowdwork platforms treat microtasks as indivisible units; however, in this article, we propose that there is value in re-examining this assumption. We argue that crowdwork platforms can improve their value proposition for all stakeholders by supporting subcontracting within microtasks. After describing the value proposition of subcontracting, we then define three models for microtask subcontracting: real-time assistance, task management, and task improvement, and reflect on potential use cases and implementation considerations associated with each. Finally, we describe the outcome of two tasks on Mechanical Turk meant to simulate aspects of subcontracting. We reflect on the implications of these findings for the design of future crowd work platforms that effectively harness the potential of subcontracting workflows.